Determination of Dowry in the Bugis-Makassar Community: An Islamic Law Perspective on Local Cultural Practices - Muhammadong Muhammadong (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
This study aims to investigate the practice of establishing dowry within the Bugis-Makassar community and to assess its alignment with the tenets of Islamic law and dominant local cultural norms. This study utilizes a qualitative methodology grounded in a normative-sociological framework. Data were gathered by literature review, analysis of Islamic legal sources, and scrutiny of customary behaviors within Bugis-Makassar marital traditions. The results show that setting the dowry is not only seen as a religious duty in the marriage contract, but also as a sign of respect, family honor, and cultural identity. In reality, the amount of dowry is frequently determined by social standing, education, ancestry, and familial consensus. From the standpoint of Islamic law, the establishment of dowry is permitted, provided it does not cause difficulty to the groom, does not include compulsion, and is consistent with the ideal of ease in marriage. Thus, it can be inferred that the practice of dowry determination within the Bugis-Makassar community exemplifies a reconciliation between Islamic legal principles and the maintenance of local cultural values, provided it does not contravene Islamic teachings.